The politics of related lending - Michael Halling; Pegaret Pichler; Alex Stomper (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
We analyze the profitability of government-owned banks' lending to their owners, using a unique data set of relatively homogeneous government-owned banks; the banks are all owned by similarly structured local governments in a single country. Making use of a natural experiment that altered the regulatory and competitive environment, we find evidence that such lending was used to transfer revenues from the banks to the governments. Some of the evidence is particularly pronounced in localities where the incumbent politicians face significant competition for reelection.
Keywords: G21; G38; L32; 330; politics and finance; bank regulation; related lending